IDENTIFIKASI MAKANAN BERESIKO DI SMK KESEHATAN JAYAPURA: EDUKATOR KESEHATAN TEMAN SEBAYA - Eva Susanty Simaremare; Allowisya Futwembun; Rusnaeni Rusnaeni; Elsye Gunawan; Rani Dewi Pratiwi; Septriyanto Dirgantara (JURNAL PENGABDIAN PAPUA, 2018)
Food is all products consumed by humans either in the form of raw, semi-finished, or finished materials which include industrial products, restaurants, catering, traditional food or snacks. Students are often wrong to choose the healthy foods or snacks in schools.  This  study aims  to  support  students  of  SMK  Kesehatan  Jayapura  in identifying hazardous food in school or at home. Therefore they became health educator for others students. This  activity was conducted at SMK Health Analysis Jayapura on September 14, 2017 with several methods that were: 1). Lectured in small group; 2). Preparation administration at FMIPA Uncen and SMK, 3). activities lectured and discussions of risky food, (3) evaluation and data analysis through questionnaires istributed. The number of participants were 134 people. From the results showed that 8.2% of students know how to choose healthy food. About 5.2% of participants had been got the same activity. And 90.3% of the students committed to assist others in choosing good food.Keywords: Identification, food, SMK Health, Jayapura, snacks